2020
DOI: 10.18203/2394-6040.ijcmph20203373
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and nutritional status of late adolescent in an urban area of Western Maharashtra: cross sectional study

Abstract: Background: Prevalence of overweight and obesity is rapidly increasing among adolescent age. One of the reasons is change in lifestyle and behavior practices. Adolescent population and health of adolescents have a special concern. In late adolescence there is transition from school to college or university. This transition to college life often worsens lifestyle and dietary habits among late adolescents. Present study was carried out to assess lifestyle and nutritional status of late adolescent.Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Snack is a ready-to-eat food and beverage prepared and sold by hawkers or vendors in streets or other public places. 19,20 Based on the observation, the main ingredients mostly used were eggs and flour. Reports on microbial contamination usually come from chicken or ice cubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snack is a ready-to-eat food and beverage prepared and sold by hawkers or vendors in streets or other public places. 19,20 Based on the observation, the main ingredients mostly used were eggs and flour. Reports on microbial contamination usually come from chicken or ice cubes.…”
Section: Discussionmentioning
confidence: 99%
“…5 The adolescent population and health is a very special issue and is the focus of attention globally for various reasons. 6 A study concluded that adolescents have a habit of low consumption of fruits, green vegetables, and milk; consume lots of snacks, sweets, and soft drinks; and skip breakfast. The result of this eating habit is the continuous increase in adiposity among children.…”
mentioning
confidence: 99%
“…Trên thế giới, nghiên cứu cắt ngang mô tả của Wegayehu Zeneb được thực hiện trên 381 thanh thiếu niên kết quả tỷ lệ suy dinh dưỡng thấp còi và nhẹ cân lần lượt là 18,6% và 18,9% [2]. Nghiên cứu của Jyotia Landge với phương pháp nghiên cứu cắt ngang được thực hiện với 140 sinh viên cuối tuổi vị thành niên từ 17-19 tuổi, tỷ lệ thừa cân và béo phì chung lần lượt là 49 (35,0%) và 29 (20,7%) [3]. Tại Việt Nam, nghiên cứu của Ngô Hồng Nhung, Trương Thị Thùy Dương (2021) ở học sinh khối 10 trường trung học phổ thông Gang Thép, thành phố Thái Nguyên có tỷ lệ suy dinh dưỡng thể gầy còm ở học sinh khá cao suy dinh dưỡng mức độ vừa chiếm chủ yếu 12,0%, suy dinh dưỡng mức độ nặng chỉ chiếm 0,7% [4].…”
Section: đặT Vấn đềunclassified